Comparative analyses of the Pan lineage reveal selection on gene pathways associated with diet and sociality in bonobos. (11th December 2020) - Kovalaskas, Sarah; Rilling, James K.; Lindo, John
Abstract: Chimpanzees ( Pan troglodytes ) and bonobos ( Pan paniscus ) diverged into distinct species approximately 1.7 million years ago when the ancestors of modern‐day bonobo populations were separated by the Congo River. This geographic boundary separates the two species today and the associated ecological factors, including resource distribution and feeding competition, have likely shaped the divergent social behavior of both species. The most striking behavioral differences pertain to between group interactions in which chimpanzees behave aggressively towards unfamiliar conspecifics, while bonobos display remarkable tolerance. Several hypotheses attempt to explain how different patterns of social behavior have come to exist in the two species, some with specific genetic predictions, likening the evolution of bonobos to a process of domestication. Here, we utilize 73 ape genomes and apply linkage haplotype homozygosity and structure informed allele frequency differentiation methods to identify positively selected regions in bonobos since their split from a common pan ancestor to better understand the environment and processes that resulted in the behavioral differences observed today. We find novel evidence of selection in genetic regions that aid in starch digestion (AMY2) along with support for two genetic predictions related to self‐domestication processes hypothesized to have occurred in the bonobo. We also find evidence for selection on neuroendocrine pathways associated with social behavior including the oxytocin, serotonin, and gonadotropin releasing hormone pathways. Abstract : Comparative whole genome analyses between bonobo and chimpanzee populations reveal positive selection in bonobos related to diet, sociality, and sexual behavior.